Swami Vivekananda: The Complete Biography- Vol.III - Sri Anand (New Delhi Atlantic Publishers)
The book in four volumes is a comprehensive biography of Swami Vivekananda, the great philosopher of the East, incorporating information from most authentic sources. The book chronologically describes all the events in the life of Vivekananda right from his birth to demise of the great soul along with a brief history of his family background. It explores the transformation of Narendranath into Swami Vivekananda under Sri Ramakrishna Paramahansa.
Keywords: Biography